Isokinetic Training Program to Improve the Physical Function and Muscular Performance of an Individual with Partial Injury of the Medial Meniscus: A Case Report - Karen Obara; Pedro Silva; Mariana Silva; Fagner Mendes; Gabriel Santiago; Ihan Oliveira; Jefferson Cardoso (North American Sports Medicine Institute, 2023)
# Background and Purpose One of the best alternatives for the treatment of meniscal injuries in relation to surgical procedures, is exercise. This case report aimed to describe the effects of isokinetic training and a neuromuscular/proprioceptive exercise program on muscle performance and physical function in an individual after a rupture of the posterior horn of the medial meniscus. # Study Design Case report. # Case Description A 40-year-old man injured his right knee during a soccer match, with a partial lesion of the medial meniscus confirmed by magnetic resonance imaging. He completed an isokinetic training program in addition to exercises that targeted proprioception (22 sessions, 11 weeks) to improve physical function and performance, which were assessed before and after treatment and at a six-month follow-up. An individual with similar anthropometric characteristics was chosen to be used as a control for understanding the patient's assessment values. # Outcomes Muscular performance of the knee flexors and extensors was evaluated isokinetically using the Biodex System-4 in a concentric mode at angular velocities of 60, 120, and 300 °/s . The main results indicated that after 11 weeks, the peak torque normalized to body mass (PT/BM), at 60 °/s of the knee extensors remained unchanged (2.54 N.m/kg) (below the control value - 3.06 N.m/kg), and at the six-month follow-up, increased by approximately 20% (3.08 N.m/kg). For the hamstrings, at 60 °/s, an increase of 18 % occurred after intervention (1.98 N.m/kg) and by approximately 30 % at the six-month follow-up (2.12 N.m/kg) - values much higher than the control 1.55 N.m/kg). This increase in the PT/BM was also reflected in the Hamstrings:Quadriceps ratio (78 %) after treatment which improved at follow-up (68 %). # Discussion The results showed that the isokinetic training and neuromuscular/proprioceptive exercises improved the muscle performance of the knee flexors and extensors, after eleven weeks of intervention, and remained (or continued to improve) at the six-month follow-up. # Level of evidence 5, single case report